Effect of Oil-Palm-Empty-Fruit-Bunch Granular Organic Fertilizer on The Yield 0f Oil Palm Fruit - Indah, Susi Puspita; Hermansyah, Hermansyah; Hasanudin, Hasanudin; Marwanto, Marwanto (Akta Agrosia, 2017)
Oil Palm has a strategic role in the Indonesian economy. The use of anorganic fertilizers in the cultivation of Oil Palm is to add nutrients to optimize the growth and yield of plants. The use of anorganic fertilizers significantly  increase crop production, but the use of anorganic fertilizers in a relatively long time period has  negative impact on soil conditions. The use of organic fertilizers can be an alternative in reducing the negative impact of the use of anorganic fertilizers. Compost of empty fruit bunch (EFB) of oil palm has the potential to substitute most of the nutrients needed by plants. This study aimed to determine the effect of local organic fertilizers on yields of oil palm. The research was implemented from January 2016 until March 2016, in the oil palm plantation area of PT Bio Nusantara Bengkulu, Village of Pondok Kelapa, Central Bengkulu Regency, Bengkulu.  Dose of EFB was as treatment in this study, consisted of  control,  4 kg EFB /plant, 8 kg /plant,  12 kg /plant, 16 kg /plant. The treatment was repeated three times with 10 plants per treatment unit in order to obtain 150 samples. The results showed that the dose 21.03 kg EFB can improve the greenish of leaves with the result of 78.65. Dose of EFB 15.38 kg/plant was able to increase the weight of loose/detached fruit to 12.22 grams. The  10.5 kg mesocarp thickness reached 0.96 cm when the plant was treated with EFB 10.5 kg/plant.Keywords: compost, empty fruit bunch, oil palm, organic fertilizer, yield